Android-based Mail Management Information System in Desa Adat - Hariwijaya, Awen; Sudana, Oka; Cahyawan Wiranatha, Anak Agung Ketut Agung (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2022)
Desa Adat is one of the traditional institutions in Bali. Based on a survey and interview in Desa Pakraman Sesetan gives proof that mail management and archiving are still done conventionally. This research’s purpose is to build a system that can increase mail management’s efficiency in Desa Adat. Android-based application allows its user to do mail management from anywhere and anytime with the phone-optimized user interface. System is developed using Flutter Framework on the front-end side and Laravel Framework on the back-end side. System testing is done by using the Blackbox Method and PSSUQ Method. System testing’s result using Blackbox Method gives the fact that the system’s functionality already runs well. System testing’s result using PSSUQ Method gives the fact that the system has been declared good.